Dange:: Sinkronisasi Gereja Katolik terhadap Budaya Dayak Kayan Mendalam - Efriani Efriani; Donatianus BSE. Praptantya; Jagad Aditya Dewantara (Jurnal Masyarakat dan Budaya, 2020)
This research is motivated by the phenomenon of a blend of Dayak Kayan Mendalam customs and the rites of the Catholic Church in the dange tradition. Dange is a form of fusion of the Catholic Church's sacraments with local culture on the island of Borneo. Dange experienced development together with the Catholic Dayak Kayan Mendalam people. This research was conducted with interviews and field observations about the Dange tradition in the Catholic Church in the Mendalam parish in the middle of Dayak Kayan Mendalam, West Kalimantan. The synchronization between Dayak Kayan Madalam culture and the Rite of the Catholic Church was encouraged by Father Aloysius Ding, SMM as a native of Dayak Kayan Mendalam. Synchronization is done through the translation of the rites of the Catholic Church into the Dayak Kayan Mendalam.